Mycoplasma pneumonia Infection Is Associated With an Increased Risk of Systemic Lupus Erythematosus: A Nationwide, Retrospective Cohort Study - Chu, Kuo-An; Ou, Ting-Yun; Hung, Wei-Hsin; Sung, Jie; Chen, Weishan; Lin, Cheng-Li; Hung, Yao-Min; Wei, James Cheng-Chung (Frontiers in Microbiology, 2022)
Abstract Background: Infections may play a role in the development of systemic lupus erythematosus (SLE). Objective: To assess the link between Mycoplasma pneumonia (M. pneumonia) infection and the incidence of SLE. Method: We conducted a retrospective cohort study, which identified 116,043 hospitalized patients with M. pneumonia between 2000 and 2012 from the Taiwan National Health Insurance Research Database, and compared them with 447,839 matched inpatients who had never been diagnosed with M. pneumonia infection (at a 1:4 ratio, matched by age, gender and index year). Their comparative risk of developing SLE was evaluated. The follow-up period was defined as the time from the initial diagnosis of M. pneumonia infection to the date of SLE diagnosis, or 31st December 2013. The incidence rates of SLE were assessed in people with and without M. pneumonia infection. Cox proportional hazard models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs), with the uninfected group used as the reference. Results: The adjusted HR of SLE for the M. pneumonia group was 2.97 with 95% CI = 2.18-4.05 compared with the uninfected group. The risk was most significantly higher within 0.5 years after the M. pneumonia infection with an adjusted HR of 6.18 (95% CI = 3.82-9.97, p<0.01). The adjusted HR for SLE from 0.5 to 2 years and from 2 to 5 years after M. pneumonia infection was 1.59 (95% CI = 0.70-3.59, p=0.27) and 2.42 (95% CI=1.22-4.81, p=0.01), respectively. Conclusions: The incidence of SLE was significantly higher in subjects infected with M. pneumoniae.